LEGAL CONSTRUCTION AND IMPLICATIONS RELATED TO PROTECTION OF MAKING SEX TAPE WITH A COUPLE - Furqania, Mriya Afifah; Michael, Tomy (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
This study aims to analyze the Indonesian laws and regulations concerning the protection of intimate video makers. The research was conducted by analyzing the Pornography Law, the Information and Electronic Transaction Law, the Government Regulation on the Implementation of Electronic Transaction Systems, and the Regulation of the Minister of Information Communication on Personal Data Protection. This research found that data/documents that are made for oneself and for their own interests which are not prohibited by law and included to one of the privacy rights that must be protected by every human being and by the state. The making of this intimate video is included in the privacy rights to enjoy life and should not be contested. Activities contained in the video can range from holding hands, hugging, kissing to having sex with consent. Therefore, if there are those who oppose rights such as acquisition and distribution without consent, the owner of the personal data can file a lawsuit for damages and have a right to erase their electronic documents.Keywords: intimate video; protection; sexual lawAbstrakPenelitian ini bertujuan untuk menganalisis peraturan perundang-undangan Indonesia yang memuat tentang perlindungan terhadap pembuat video mesra. Penelitian dilakukan dengan menganalisis Undang-Undang Pornografi, Undang-Undang Informasi dan Transaksi Elektronik, Peraturan Pemerintah tentang Penyelenggaraan Sistem Transaksi Elektronik serta Peraturan Menteri Komunikasi dan Informasi tentang Perlindungan Data Pribadi. Penelitian ini menemukan bahwa data/dokumen yang dibuat untuk diri sendiri dan kepentingan sendiri bukanlah hal yang dilarang oleh undang-undang dan justru harus dilindungi baik oleh tiap manusia maupun negara. Pembuatan video mesra ini termasuk dalam hak pribadi untuk menikmati hidup dan tidak boleh diganggu gugat. Aktivitas yang termuat dalam video tersebut bisa dari bergandengan tangan, berpelukan, berciuman hingga berhubungan badan yang dilakukan atas persetujuan. Oleh sebab itu jika terdapat pelanggaran terhadap hak seperti perolehan dan penyebarluasan tanpa persetujuan, pemilik data pribadi dapat mengajukan gugatan kerugian dan mengajukan permohonan untuk menghapus data tersebut.